Subjective Well-Being pada Pelaku Wirausaha dalam Komunitas Yukbisnis - Ikhsan Badruz Zaman (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study aims to understand the subjective experiences of entrepreneurs who are members of the YukBisnis community in building and maintaining their psychological well-being Subjective Well-Being (SWB). Using a qualitative phenomenological approach, in-depth interviews were conducted with five informants from various business backgrounds. Thematic analysis revealed three main themes, the community as a space for fulfilling basic psychological needs, the paradox of well-being between entrepreneurial meaning and personal pressure, and collectivist culture as a lens for interpreting SWB. The YukBisnis community functions not only as a business learning forum but also as a social ecosystem that supports members' autonomy, competence, and relatedness. This study highlights the critical role of community support in enhancing entrepreneurial well-being, especially within Indonesia's collectivist cultural context. The findings contribute to the development of community-based positive psychology theory and serve as a basis for more human-centered and contextualized MSME support policies.